Kantin Sehat dalam Meningkatkan Kebiasaan Makan Sehat pada Siswa Sekolah Dasar - Khaerunisa, Ines; Nisa, Khansa Khairun; Handayani, Nur Afifah; Liandi, Nura Alisha; Rahayu , Rina; Prihantini, Prihantini (Lembaga Intelektual Muda (LIM) Maluku, 2025)
Nutrition can be one of the main problems in school-age children. Malnutrition can trigger drowsiness and lack of enthusiasm, so that the learning process at school is disrupted. The problem of undernutrition and poor nutrition is directly influenced by food consumption patterns and infectious diseases. This study aims to determine the role of healthy canteens in improving healthy eating habits in elementary school students. This research uses a qualitative approach through the literature study method. Data collection was carried out by collecting various relevant and up-to-date references, including research articles published on Google Scholar, books, and other documents related to the substance of the problem in this study. Data analysis is carried out qualitatively through the stages of data reduction, data presentation, and conclusion drawing. The results of the analysis show that the school canteen program which began to be held in 2009 by the Ministry of National Education is one of the interventions to maintain food safety, especially in schools in Indonesia. Nutritional intake is quite important for the growth and development of children. The healthy canteen program in schools is an effort to encourage healthy eating habits from an early age. Healthy canteens provide nutritious food and become a means of nutrition education for students. Healthy canteens provide nutritious food and become a means of nutrition education for students